IL-22 and its receptors are increased in human and experimental COPD and contribute to pathogenesis. Issue 1 (18th July 2019) - Starkey, Malcolm R.; Plank, Maximilian W.; Casolari, Paolo; Papi, Alberto; Pavlidis, Stelios; Guo, Yike; Cameron, Guy J.M.; Haw, Tatt Jhong; Tam, Anthony; Obiedat, Ma'en; Donovan, Chantal; Hansbro, Nicole G.; et al.
Chronic obstructive pulmonary disease (COPD) is the third leading cause of morbidity and death globally. The lack of effective treatments results from an incomplete understanding of the underlying mechanisms driving COPD pathogenesis. Interleukin (IL)-22 has been implicated in airway inflammation and is increased in COPD patients. However, its roles in the pathogenesis of COPD is poorly understood. Here, we investigated the role of IL-22 in human COPD and in cigarette smoke (CS)-induced experimental COPD. IL-22 and IL-22 receptor mRNA expression and protein levels were increased in COPD patients compared to healthy smoking or non-smoking controls. IL-22 and IL-22 receptor levels were increased in the lungs of mice with experimental COPD compared to controls and the cellular source of IL-22 included CD4 + T-helper cells, γδ T-cells, natural killer T-cells and group 3 innate lymphoid cells. CS-induced pulmonary neutrophils were reduced in IL-22-deficient ( Il22 −/− ) mice. CS-induced airway remodelling and emphysema-like alveolar enlargement did not occur in Il22 −/− mice. Il22 −/− mice had improved lung function in terms of airway resistance, total lung capacity, inspiratory capacity, forced vital capacity and compliance. These data highlight important roles for IL-22 and its receptors in human COPD and CS-induced experimental COPD. IL-22 and its receptors are increased in both human and experimental chronic obstructive pulmonary disease (COPD). IL-22 drives neutrophilic inflammation and impaired lung function in experimental COPD. http://bit.ly/2Vsri6T